Cash Waqf Linked Sukuk and Economic Empowerment: A Grounded Theory from Indonesia - Mohammad Gally Tawakkal; Muhammad Iman Kurniawan; Faathima (Jambi Tuah Tengganai, 2026)
Cash Waqf Linked Sukuk (CWLS) constitutes a hybrid Islamic financial instrument that integrates cash waqf mobilization with sovereign sukuk issuance to finance socio-economic projects without depleting the principal endowment. While Indonesia possesses a cash waqf potential estimated at IDR 180 trillion per annum, realized collection remains marginal, and existing CWLS series have absorbed only a fraction of this latent capital. This study examines how the management of productive waqf can be optimized through the CWLS scheme to strengthen the economic empowerment of the ummah (Muslim community). Adopting a qualitative research design with a constructivist grounded theory approach, the study analyzes 47 peer-reviewed publications issued between 2018 and 2025 alongside regulatory texts, official press releases of the Ministry of Finance Directorate General of Budget Financing and Risk Management (DJPPR), and impact reports of the Indonesian Waqf Board (BWI), employing theoretical sampling, three-stage coding (open, axial, and selective), and the constant comparative method to construct a substantive theory of CWLS optimization. The findings reveal four structural bottlenecks low waqf literacy, fragmented governance among nazhir, sub-optimal coupon channeling design, and limited digital infrastructure that constrain the redistributive efficacy of CWLS. The study proposes an integrated optimization framework anchored on five pillars: First, regulatory harmonization grounded in maqāṣid al-sharī'ah, Second, professionalization and certification of nazhir, Third, digital fundraising platforms leveraging Islamic fintech, Fourth, productive sectoral targeting aligned with the Sustainable Development Goals (SDGs), and Fifth, impact-based monitoring through Waqf Core Principles. The framework offers a replicable governance model for OIC member states and contributes to the Islamic social finance literature by reframing CWLS as a developmental, rather than purely philanthropic, instrument.